Implementasi Manajemen Sumber Daya Manusia dalam Meningkatkan Kedisiplinan Santri di Pondok Pesantren Hidayatul Mubtadiin Lampung Selatan - Dwi Ayu Lestari; Nurul Hidayati Murtafiah; Nur Widiastuti (Journal on Education, 2023)
This study aims to find out about the implementation of human resource management in improving the discipline of students at the Hidayatul Mubtadiin Islamic Boarding School, South Lampung. This research includes field research. The method used in this study is to use the method of observation, interviews, and documentation. The data analysis technique used is an interactive model and data triangulation to check the validity of the data. The results showed that planning for implementing human resource management in improving student discipline at the Hidayatul Mubtadiin Islamic Boarding School in Sidoharjo village was carried out and determined in the form of a joint management meeting for both men and women. Human Resource Development Program in Improving Disciplinary Competence of students which are routine and incidental, namely: 1) Congregational Prayer, 2) Morning Call, 3) Islamic Studies, 4) Training Motivation, 6) Routine evaluation, 7) Giving sanctions, 8), queue to eat according to the specified time. Evaluation of the Human Resource Development Management program in Improving the discipline of students at the Hidayatul Mubtadiin Islamic Boarding School is carried out in the form of monitoring and supervision from the Management (ustadz and ustadzah) of the Islamic Boarding School and assessing the attitude of the students carried out by the administrators (ustad and ustadzah) at the Hidayatul Mubtadiin Islamic Boarding School by means of notes through the black book and how many of these students have a letter of violation signed on the mat.